Pension wealth and household savings in Europe: Evidence from SHARELIFE - Rob Alessie; Viola Angelini; Peter van Santen (Sveriges Riksbank, 2013)
We use recently collected retrospective survey data to estimate the displacement effect of pension wealth on household savings. The third wave of the Survey of Health, Ageing and Retirement in Europe, SHARELIFE, collects information on the entire job history of the respondent, a feature missing in most previous studies. We show that addressing measurement error problems is crucial to estimate the displacement effect when using survey data. We find that each euro of pension wealth is associated with a 47 (61) cent decline in non-pension wealth using robust (median) regression. In the presence of biases from measurement errors and omitted (unobserved) variables, we estimate a lower bound to the true offset between 17% and 30%, significantly different from zero. Instrumental variables regression estimates, although less precise, suggest full displacement.
Keywords: D91; H55; D31; 330; Displacement effect; Lifetime income; Retrospective survey; Measurement error; Lebenseinkommen; Altersvorsorge; Sparen; Statistischer Fehler; Instrumentalvariablen-Schätzmethode; EU-Staaten